2013
DOI: 10.1063/1.4775740
|View full text |Cite
|
Sign up to set email alerts
|

Are rare, long waiting times between rearrangement events responsible for the slowdown of the dynamics at the glass transition?

Abstract: The dramatic slowdown of the structural relaxation at the glass transition is one of the most puzzling features of glass dynamics. Single molecule orientational correlation times show this strong Vogel-Fulcher-Tammann temperature dependence typical for glasses. Through statistical analysis of single molecule trajectories, we can identify individual glass rearrangement events in the vicinity of a probe molecule in the glass former poly(vinyl acetate) from 8 K below to 6 K above the glass transition temperature.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…6, R(τ ) decreases dramatically with τ in general. Detailed examinations of individual particle trajectories show that this is due to the abundance of back-and-forth hopping motions at low T widely studied in the literature [38,[45][46][47][48][49][50][51][52]. Since R(τ ) is a net hopping rate not registering the back-and-forth parts of the hops, at large τ , it underestimates the true hopping rate and is instead a better indicator of particle mobility describing long-time motions in the diffusive regime.…”
Section: B Particle Hopping Ratesmentioning
confidence: 97%
See 1 more Smart Citation
“…6, R(τ ) decreases dramatically with τ in general. Detailed examinations of individual particle trajectories show that this is due to the abundance of back-and-forth hopping motions at low T widely studied in the literature [38,[45][46][47][48][49][50][51][52]. Since R(τ ) is a net hopping rate not registering the back-and-forth parts of the hops, at large τ , it underestimates the true hopping rate and is instead a better indicator of particle mobility describing long-time motions in the diffusive regime.…”
Section: B Particle Hopping Ratesmentioning
confidence: 97%
“…Surface effects penetrate up to z 5.5σ for τ = 20 and 40, but reach deeper to z 4.5σ for τ = τ max . To establish this more clearly, we numerically evaluate an integrated hopping event correlation defined by Particle back-and-forth motions have long been studied in glassy systems [38,[45][46][47][48][49][50][51][52] and cause the main peak at r = 0 in Fig. 11(b)-(c).…”
Section: Hopping Event Correlationsmentioning
confidence: 99%
“…Common approaches make use of (i) the collective motion of particles in the configuration phase space [18][19][20], (ii) the motion of a particle relative to its neighbors [21][22][23], or (iii) the single particle displacement [24]. It has recently been shown that these criteria provide similar results for the distribution of relaxation events [25]. Typical dynamics of a particle in a glassy state consists of in-cage high-frequency rattling motion accompanied by intermittent cage-breakage jumps (structural relaxation events).…”
mentioning
confidence: 99%
“…For the higher studied temperatures, the ratio is close to one, as expected for standard liquid conditions 61 , but for lower temperatures the ratio grows, as in the fluctuation dominated regime of supercooled liquids, where this is a signature of the breakdown of Stokes-Einstein relations 62,63 . Persistence times, defined as the average waiting time from any given point in the trajectory of a single molecule, until the next jump event, are comparable to the structural relaxation time t α in simple models of glass dynamics 64 . The probability distribution of persistence times is comparable to typical results of bulk experi- ments, due to the time-weighted nature of typical observations.…”
Section: Resultsmentioning
confidence: 99%